2008
DOI: 10.1111/j.1551-2916.2008.02812.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective Synthesis of Lithium Ion‐Conductive β‐LiVOPO4 Crystals via Glass–Ceramic Processing

Abstract: A glass-ceramic processing is applied to a glass with the composition of 33.3Li 2 O-33.3V 2 O 5 -33.3P 2 O 5 (mol%) in order to synthesize lithium ion-conductive b-LiVOPO 4 crystals being a potential candidate for cathode materials in lithium ion batteries. It is found that three crystalline phases of a-LiVOPO 4 , Li 2 VPO 6 , and b-LiVOPO 4 are formed during the crystallization and a-LiVOPO 4 crystals formed initially transform into b-LiVOPO 4 . The glass-ceramics consisting of almost mainly b-LiVOPO 4 crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…No other common impurities such as Li 3 PO 4 , Li 2 VPO 6 and V 2 O 5 have been observed. 18,29 Several control try-outs have been conducted to establish the factors that govern the formation of hollow a-LiVOPO 4 microspheres including effects of (1) temperature, (2) time, (3) precursor and (4) solvent. when the reaction duration has reached at 20 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No other common impurities such as Li 3 PO 4 , Li 2 VPO 6 and V 2 O 5 have been observed. 18,29 Several control try-outs have been conducted to establish the factors that govern the formation of hollow a-LiVOPO 4 microspheres including effects of (1) temperature, (2) time, (3) precursor and (4) solvent. when the reaction duration has reached at 20 h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, the high temperature a-LiVOPO 4 phase has more open framework with large Li sites in which Li atoms are loosely bound as compared to the metastable b-LiVOPO 4 . 26 Till now LiVOPO 4 has been synthesised by high temperature ceramic routes, 16,[27][28][29] hydrothermal methods 18,26 or combination of these methods to synthesize VOPO 4 followed by lithiation to produce LiVOPO 4 . 16,17 However, these methods suffer from the unavoidable high-energy utilization and polydispersed growth of the grains due to the high processing temperatures (generally at 600-900 C) which also increase the material cost.…”
Section: Introductionmentioning
confidence: 99%
“…Crystallization of glass is a method for fabrication of dense condensed materials with desired shapes and also nanostructures [12][13][14]. Nagamine et al [15,16] also applied the glass crystallization method to the syntheses of Li 3 Fe 2 (PO 4 ) 3 and β-LiVOPO 4 ceramics. Thokchom and Kumar [17] reported lithium ion conductive glass-ceramics consisting of Li 1+x Al x Ti 2−x (PO 4 ) 3 in the system of Li 2 O-Al 2 O 3 -TiO 2 -P 2 O 5 , and recently Pang et al [18] tried to pattern crystal lines of Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 on the glass surface by a laser irradiation technique.…”
Section: Introductionmentioning
confidence: 99%
“…LiVOPO 4 has different crystallographic phases such as tetragonal α-LiVOPO 4 [7,8] and orthorhombic β-LiVOPO 4 [6,[9][10][11], and it has been reported that β-LiVOPO 4 exhibits excellent electrochemical performances as lithium-ion batteries [6].…”
Section: Introductionmentioning
confidence: 99%